EKSISTENSI KIAI DALAM PENGEMBANGAN TRADISI ISLAM INDONESIA - Sayfa Auliya Achidsti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
Locality is the closest entity toward the society. Moreover in Indonesia,this problem should be located as the stepping stone to view howthe people live, their need, and the reason why do they live in such way.This existence relates each other forming a civil society. This article discussesthe relationship between religion and society as an important factorwhich influences much on the Islamic scholars’ position and all theiractivities in the society. In traditional Javanese society, the Islamic scholarsare more positioned as having a strategic social function in a society.